TOPOLOGY OPTIMIZATION OF MOTORCYCLE FOOT-PEDAL - CHEN YaJuan; JIA ZhiChao; GAO Xu (Jixie qiangdu)
By using FEA,the strength and stiffness characteristics of motorcycle foot-pedal under extreme loads conditions with driver and passenger were analyzed. Based on these,topology optimization was conducted with inner ribs as design domains using variable density method. Meanwhile,one new model was obtained according to the topological optimum results and the feasibility of structure is verified. The deficiency of strength and stiffness of previous design is resolved. In this way,it can shorten the development cycle and provide the theoretic guidance for the design of homogeneous products.